Addressing the barriers to driver licensing for Aboriginal people in New South Wales and South Australia - Kathleen Clapham; Kate Hunter; Patricia Cullen; Yvonne Helps; Teresa Senserrick; Jake Byrne; James E. Harrison; Rebecca Q. Ivers (Elsevier, 2017)
Abstract Objective: Low rates of driver licensing have been linked to increased risk of transport‐related injury, and reduced access to health services, employment and educational opportunities in the Aboriginal population. This paper reports on how barriers to obtaining a driver licence are being addressed in four Aboriginal communities in New South Wales and South Australia. Methods: Qualitative data were collected over a four‐month period in 2013. Interviews with Aboriginal and non‐Aboriginal stakeholders (n=31) and 11 focus groups with Aboriginal participants (n=46) were analysed thematically using a framework approach. Results: Factors facilitating licensing included: family support, professional lessons, alternative testing and programs that assist with literacy, fines management, financial assistance and access to a supervising driver. Stakeholders recommended raising awareness of existing services and funding community‐based service provision to promote access to licensing. Discussion: Facilitating licence participation requires systemic change and long‐term investment to ensure interagency collaboration, service use and sustainability of relevant programs, including job search agencies. Implications for public health: The disadvantage faced by Aboriginal people in driver licensing is a fundamental barrier to participation and a social determinant of health. Understanding the factors that promote licensing is crucial to improving access for under‐serviced populations; recommendations provide pragmatic solutions to address licensing disadvantage.